An Innovative Mathematical Model: A Key to the Riddle of HbA1c - Mahdi Kahrom (International Journal of Endocrinology)
HbA1c is a standard clinical assessment of glycemia and the basis of most data relating glycemic control to complications. While daily blood glucose testing gives a picture of day-to-day fluctuations, the HbA1c test offers an overview of how well glucose has been controlled over the past 4 months. I devised an innovative mathematical model to describe novel equations governing HbA1c which enables analysis of HbA1c behavior and provides emerging new concepts in assessment of diabetes management. Linear relationship of HbA1c and mean plasma glucose along with the kinetic analysis of HbA1c formation has been used as the basic suppositions to construct this model. The main application of this devised model is prediction of mean plasma glucose at any desired point in time after a change in therapy and with great certainty. This model also appraises the pattern of HbA1c changes over time and provides a unique opportunity to address common mistakes and misconceptions in routine application of HbA1c that could have potentially important implications on diabetes control.